Community Perspectives on the Environmental, Social, and Economic Impacts of the Tomohon International Flower Festival - Ni Kadek Swandewi; Clearesta Adinda; Ingryt Grity Adipati; I Gusti Agung Febrianto (Penerbit Goodwood, 2024)
Purpose: The purpose of this research is to evaluate the perceptions of the local community regarding the economic, socio-cultural, and environmental impacts of the Tomohon International Flower Festival (TIFF). Specifically, the study aims to understand how the residents of Tomohon view the festival's contributions to their economic well-being, social cohesion, cultural preservation, and environmental sustainability.Methodology: This research used an exploratory approach to analyse residents' perceptions of the economic, socio-cultural, and environmental impacts of festival activities in Tomohon. Results: The research shows that the Tomohon International Flower Festival (TIFF) is positively viewed by the local community, boosting income, job creation, and regional revenue. It enhances social interactions, cultural pride, and supports education. However, concerns about waste and its impact on the city's aesthetics highlight environmental sustainability issues.Conclusions: TIFF positively impacts the economy, society, and environment but raises concerns about waste management, highlighting the need for better sustainability practices.Limitations: The data reflects respondents' views at a specific point in time and may be influenced by personal experiences, biases, or limited knowledge of economic, socio-cultural, and environmental factors. Additionally, the sample size, though sufficient for exploratory analysis, may not fully represent the Tomohon population, limiting the generalizability of the findings.Contribution: This article enhances understanding of the socio-economic and environmental impacts of large cultural events like the Tomohon International Flower Festival (TIFF) from the local community's perspective. It also offers guidance for organizers and policymakers in optimizing festival benefits while addressing community concerns for more sustainable and inclusive planning.